Grit in the path to e-learning success - Aparicio, M. (2017)
E-learning systems are emerging in many settings of our society. Schools, universities, and several other organizations use these systems. E-learning systems allow learning anytime and anywhere. This medium may seem to be the answer to all learning barriers, but the effect of non-cognitive skills on the success of e-learning systems is yet to be explored. Latest studies demonstrate that students with high grit levels, stamina in pursuing long term objectives, achieve better results in learning. In our study we propose a theoretical model studying grit as a determinant of e-learning systems success. The study was conducted on a sample of university students’ sample, and a theoretical model was validated using structural equation modeling (SEM). Results indicate that grit has positive effects on satisfaction and in students’ individual performance. The results help to improve e-learning strategies and to understand e-learning success, explained by students’ skills and systems characteristics.